Intradiscal O2O3: Rationale, Injection Technique, Short- and Long-term Outcomes for the Treatment of Low Back Pain Due to Disc Herniation. Issue 2 (May 2017) - Giurazza, Francesco; Guarnieri, Gianluigi; Murphy, Kieran J.; Muto, Mario
The management of low back pain should always start with a conservative approach; however, when it fails, intervention is required and at that moment the most appropriate choice remains unclear. Before invasive surgery, minimally invasive techniques can be adopted. In European trials and in a trans-Canadian clinical trial 03 ozone has been used successfully. In total over 50, 000 patients have been treated safely. Ozone is a gas normally present in the atmosphere with potent oxidizing power; it has been used for percutaneous intradiscal injection combined with oxygen (O2 O3 ) at very low concentrations for 15 years in Europe. The main indication is back pain with or without radicular pain but without motor deficits, which is refractory to 4-6 weeks of conservative therapies. Its mechanism of action on the disc is mechanical (volume reduction by subtle dehydration of the nucleus pulposis) and antinflammatory. The intradiscal ozone injection is performed with a thin needle (18-22 gauge) image guided by computed tomography or angiofluoroscopy and is usually complimented by periganglionic injection of corticosteroids and anesthetics. This combination gives immediate pain relief and allows time for the ozone to act. It is a cost-effective procedure that presents a very low complication rate (0.1%). The radicular pain is resolved before the back pain does, as is seen with microdiscectomy. Peer-reviewed publications of large randomized trials, case series, and meta analysis from large samples of patients have demonstrated the procedure to be safe and effective in the short and the long terms, with benefits recognized up to 10 years after treatment. We aim to review the principles of action of O2 O3 and report the injection techniques, complications, and short- and long-term outcomes.